The Technical Feasibility Analysis of Sorghum Farming In Lamunde Village Tinondo District East Kolaka Regency - Alfillah Aidin; Munirwan Zani; Lukman Yunus (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
The research objective is to analyze the technical feasibility of farming sorghum in Lamunde Village District Tinondo Regency East Kolaka. The research was carried out in the Village Lamunde District Tinondo Regency East Kolaka in July 2021. The research population, namely sorghum farmers in Lamunde Village, amounted to 25 people, while the research sample was determined using the census method. This study uses primary data and secondary data. Data collection techniques using direct interview and study method literature. Research variables include seeding, processing, land, planting, fertilizing, maintenance, pests, plant disease, and harvesting. The research was analyzed using descriptive analysis based on the scoring results. Research result shows that sorghum farming in the village of. Lamunde, Tinondo District, East Kolaka Regency is technically feasible, namely land management activities, planting activities, fertilizing activities, maintenance activities, pest control activities, and disease crops and harvesting activities included in the high category. Meanwhile, most of the seeding activities are in the medium category.